Optimization of The Dual Banking Leverage Model (DBLM) System Strategy of The Syariah Business Unit of The Regional Development Bank in Indonesia - Muhammad Hakim Sitompul; Andri Soemitra; Muhammad Yafiz (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The Sharia Business Unit (UUS) at Regional Development Banks (BPD) plays a strategic role in the development of Islamic banking in Indonesia. However, its contribution to assets, Third Party Funds, and financing remains limited despite the implementation of the Dual Banking Leverage Model (DBLM). This study aims to identify problems, solutions, and priority strategies in optimizing DBLM at UUS BPD within the framework of a dual banking system. The method used is a qualitative-quantitative approach with the Analytical Network Process (ANP), involving experts from academics, regulators, and practitioners. The results show that optimizing DBLM is a strategic and institutional issue, with the main priority being strengthening management commitment and governance, followed by improving the quality of human resources, literacy and communication, product innovation, harmonization of customer expectations, and external synergy. This study produces a DBLM optimization model based on strengthening corporate policies, aligning incentives and competencies, and integrating the values ​​of maqashid sharia. These findings contribute as a strategic reference for BPDs and regulators in strengthening UUS performance in a sustainable manner.